Characterization of epithelial subtypes of intraductal papillary mucinous neoplasm of the pancreas with endoscopic ultrasound and cyst fluid analysis - Yoon, Won Jae; Daglilar, Ebubekir S.; Mino-Kenudson, Mari; Morales-Oyarvide, Vicente; Pitman, Martha B.; Brugge, William R. (Endoscopy, 2014)
Background and study aims: Intraductal papillary mucinous neoplasm (IPMN) consists of four epithelial subtypes. There are limited data on the endoscopic ultrasound (EUS) findings and/or cyst fluid analysis of the epithelial subtypes. The objective of this study was to determine whether there are differences in EUS and cyst fluid characteristics (carcinoembryonic antigen [CEA] concentration and cytology) among the subtypes.Patients and methods: The study cohort consisted of 85 patients (median age 68 years, 40 men) with resected and histologically confirmed branch-duct or mixed-type IPMNs who underwent preoperative EUS-guided fine-needle aspiration between 1999 and 2010 for the evaluation of pancreatic cysts. EUS and cyst fluid characteristics were analyzed retrospectively and correlated with the subtypes. Results: The numbers of evaluated cystic lesions were 1 in 79 patients, 2 in 5 patients, and 3 in 1 patient. Of 92 IPMNs analyzed, gastric-type IPMNs were the most common (n = 68, 73.9 %), followed by intestinal (n = 17, 18.5 %), oncocytic (n = 5, 5.4 %), and pancreatobiliary subtypes (n = 2, 2.2 %). Gastric-type IPMNs were significantly smaller (cutoff 30 mm; P = 0.002), and less likely than other subtypes to have a mass lesion or mural nodule (P = 0.046) on EUS. Cyst fluid CEA concentration varied among the subtypes (median concentrations for gastric, intestinal, oncocytic, and pancreatobiliary types 619.8, 83.0, 5.1, and 270.0 ng/mL, respectively; P = 0.012). The presence of neoplastic epithelial cells (P = 0.624) and extracellular mucin (P = 0.208) on cytology had no association with subtypes.Conclusions: Gastric-type IPMNs, the most common subtype, are characterized by high concentrations of cyst fluid CEA, small cyst diameter, and low risk EUS imaging features.